Parent/caregiver attitudes, motivations and behaviours in relation to alcohol use among offspring aged 13-18 years: a qualitative study - Siobhan Mitchell; Rona Campbell; Georgie J. MacArthur (BMC, 2022)
Abstract Background Parental alcohol consumption and alcohol-related behaviour play a critical role in shaping adolescent alcohol use, but comparatively little is known about the perspectives of parents regarding adolescent alcohol use from qualitative studies in England. This study aimed to explore parental views and attitudes towards alcohol use during adolescence, among their offspring and among young people in general. Methods Twenty-three parents (21 mothers, 2 fathers) of children aged 13-18 years were recruited via schools, workplaces and community settings, predominantly in the West of England (n = 19) between 2017 and 2018. Data were collected via in-depth one-to-one interviews and analysed thematically, using an inductive, constructionist approach. Results Five major themes were identified in the data: (1) the parental alcohol environment, (2) balance and acceptance, (3) influences of the parental approach, (4) boundaries and parental monitoring, and (5) wider influences shaping young people's behaviour. Overall, parents were aware of the risks and consequences of alcohol use and the wide range of influences shaping drinking behaviour, and expressed broad disapproval of alcohol use among young people. However, adolescent alcohol use was viewed as inevitable, and set within a context of a tolerant drinking culture. Many parents therefore chose a balanced and reluctantly accepting approach. This approach was determined by weighing disapproval of drinking against consistency with wider culture and parental behaviour, support for autonomy of the child, and avoidance of social sanctions. Parents' responses were also determined by a desire to protect the parent-child relationship, maintain an open, communicative and trusting relationship, and ultimately limit risk and minimise harm. Various boundaries and strategies were employed to this end, including care around role modelling, gradual introductions to alcohol, boundaried provision, clear risk reduction messaging and parental monitoring. Conclusions Parents employ a range of mechanisms to reduce alcohol-related risk and to balance harms of alcohol use among their offspring against adolescent behavioural norms. A downward shift in community consumption and changing socio-cultural norms could alter the accepting context in which parents are required to navigate adolescent alcohol use.